GENDER EQUALITY - Shuhratova Zahro Shuhratovna (Academia One Publishing, 2025)
Gender equality is a set of social, economic and political processes aimed at ensuring equal rights, opportunities and conditions for men and women in society. This concept is an integral part of human rights, social justice and democratic values, and is of great importance in state policy, the education system, the labor market and cultural life. Gender equality serves the full development of not only women, but also men, expanding the economic potential and innovative capabilities of society. International experience shows that countries with a high level of gender equality achieve positive results in economic stability, quality of education and the healthcare system. Therefore, in Uzbekistan, developing this issue through legal, organizational and educational measures, reducing gender stereotypes in the public consciousness, and ensuring equal representation in all areas are among the urgent issues.
Keywords: gender equality; women's rights; men's rights